2019
DOI: 10.1016/j.amjcard.2019.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Left Ventricular Strain by Cardiac Magnetic Resonance Feature-Tracking to Predict Cardiovascular Events in Patients With and Without Heart Failure

Abstract: There is controversy regarding the utility of left ventricular (LV) mechanics assessed by featuretracking (FT)-SSFP, a readily implementable technique in clinical practice. In particular, whether LV mechanics assessed by FT-SSFP predicts outcomes in subjects with heart failure (HF) with reduced ejection fraction (HFrEF), with preserved ejection fraction (HFpEF), or without HF is unknown. We aimed to assess whether LV mechanics measured with FT-SSFP cine MRI predicts adverse outcomes. We prospectively enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
2
12
0
1
Order By: Relevance
“…Case in point, in the current study, GLS_ENDO, GLS_AVE and GLS_EPI and even LVEF were all significantly predictive of outcomes in univariable analysis, but of these only GLS_AVE remained independently associated with clinical outcomes when including NT-proBNP and age in the outcomes model. Similar to our findings, a recent CMR feature tracking study showed that GLS_AVE and GRS were predictive of outcomes in HF [ 35 ]. Different from our study, GCS_AVE was also shown to be predictive of outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Case in point, in the current study, GLS_ENDO, GLS_AVE and GLS_EPI and even LVEF were all significantly predictive of outcomes in univariable analysis, but of these only GLS_AVE remained independently associated with clinical outcomes when including NT-proBNP and age in the outcomes model. Similar to our findings, a recent CMR feature tracking study showed that GLS_AVE and GRS were predictive of outcomes in HF [ 35 ]. Different from our study, GCS_AVE was also shown to be predictive of outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…LVEF has been recognized as the routine prognostic parameter and reference standard of LV global systolic function. However, LVEF is only a representative of LV geometric change other than the function change 18 , which indicates EF may be inaccessible to identify subtle and mild degrees of LV systolic abnormalities [19][20][21][22][23] . Maciver et al reported that although longitudinal systolic strain had been reduced, EF may be normal by compensated with the increased radial wall thickness in LV hypertrophy 24 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding was evident in 50% of the patients, whereas global longitudinal strain was reportedly much lower in the anaphylaxis group than in the equivalent group with urticaria. Indeed, a lower global longitudinal strain has been recently associated with a higher long-term risk of cardiovascular morbidity and mortality in a low-risk general population (62,63).…”
Section: Kounis Syndrome As a Predominant Feature Of Anaphylaxismentioning
confidence: 99%